Formation of organized structures in systems containing alkylpyridinium surfactants and sodium poly(styrenesulfonate) - Kogej, Ksenija (Acta chimica slovenica, 2001)
Synchrotron X-ray scattering was used for structural investigations in systems of anionic polyelectrolyte and cations surfactants. The surfactant in the complexes is arranged into micellelike aggregates, which are smaller in size than free surfactant micelles. A hexagonal phase is observed in the precipitate that forms between the surfactant and the polyion under conditions of 100% binding.
Keywords: polielektroliti; poliioni; površinsko aktivne snovi; raztopine; rentgenske metode; struktura